Socioeconomic Inequalities in the Oral Health of People Aged 15-40 Years in Kurdistan, Iran in 2015: A Cross-sectional Study - Ghobad Moradi; Ardavan Moinafshar; Hemen Adabi; Mona Sharafi; Farideh Mostafavi; Amjad Mohamadi Bolbanabad (Korean Society for Preventive Medicine, 2017)
Objectives The aim of this study was to evaluate socioeconomic inequalities in the prevalence of dental caries among an urban population. Methods This study was conducted among 2000 people 15-40 years of age living in Kurdistan, Iran in 2015. Using a questionnaire, data were collected by 4 trained dental students. The dependent variable was the decayed, missing, and filled teeth (DMF) index. Using principal component analysis, the socioeconomic status (SES) of families was determined based on their household assets. Inequality was measured using the concentration index; in addition, the Oaxaca analytical method was used to determine the contribution of various determinants to the observed inequality. Results The concentration index for poor scores on the DMF index was -0.32 (95% confidence interval [CI], -0.40 to -0.36); thus, poor DMF indices had a greater concentration in groups with a low SES (p<0.001). Decomposition analysis showed that the mean prevalence of a poor DMF index was 43.7% (95% CI, 40.4 to 46.9%) in the least privileged group and 14.4% (95% CI, 9.5 to 9.2%) in the most privileged group. It was found that 85.8% of the gap observed between these groups was due to differences in sex, parents' education, and the district of residence. A poor DMF index was less prevalent among people with higher SES than among those with lower SES (odds ratio, 0.31; 95% CI, 0.19 to 0.52). Conclusions An alarming degree of SES inequality in oral health status was found in the studied community. Hence, it is suggested that inequalities in oral health status be reduced via adopting appropriate policies such as the delivery of oral health services to poorer groups and covering such services in insurance programs.